5 Extremely Low Gestational Age Neonates and Resuscitation: Perspectives of Canadian Neonatologists. (29th October 2021) - Wood, Stacie; Cheng, Anita; Coughlin, Kevin
Abstract: Primary Subject area: Neonatal-Perinatal Medicine Background: Resuscitation care planning for extremely low gestational age neonates (ELGANs) continues to be one of the most complex, ethically charged areas within paediatrics. Objectives: This study sought to determine the current attitudes and practices of neonatologists in Canada, and to assess the moral distress associated with resuscitation decisions in the ELGAN population and current practices in an era of improved neonatal outcomes. It also aimed to explore the perspectives of adopting a shared decision-making approach, where further data with regard to best interests and prognosis are gathered in an individualized manner. Design/Methods: This was a descriptive study employing an electronic survey constructed in REDCap®. The survey was distributed to neonatologists working in Level III NICUs across Canada and responses were collected from March to May 2020. Results: 65 total survey responses were received. 78% of neonatologists expressed at least some moral distress when parents request non-resuscitation between 24 weeks 0 days and 24 weeks 6 days. Prognostic uncertainty with regard to individualized long-term outcome in an era with increased chances of morbidity-free survival was the most prominent factor identified as contributing to moral distress. 70% felt they would feel less moral distress deciding about goals of care after assessing the baby's response to an initial trial of resuscitation at birth, and preferred an individualized approach to palliation decisions based on postnatal course and assessment, rather than making the decision based primarily on gestational age. Conclusion: While most current practices support the option of non-resuscitation for infants born at less than 25 weeks, there is growing evidence of moral distress among Canadian neonatologists that suggests the consideration of resuscitation at 24 weeks and above is a more realistic approach in the current era of improved outcomes. Furthermore, our results suggest that Canadian neonatologists are ethically more comfortable developing plans for care postnatally, with more evidence to support prognostication, instead of antenatally, based solely on gestational age.